New Public Financial Management and Its Legitimacy - Henry Kusuma Adikara (APMBA (Asia Pacific Management and Business Application), 2014)
This paper’s for discuss the importance of New Public Financial Management (NPFM) legitimacy. As part of the new regulation in the finance sector, NPFM promotes the application of transparency and accountability of company expenditures, risk management and value for money. However, literature study revealed that NPFM is not implemented yet in the public organization, especially in the developing countries, like Indonesia. It is predicted that it is due to socio-cultural aspect of the implementation of NPFM does not meet the society expectations. This paper explores and suggests that socio-cultural aspect should be taken into account in the implementation of NPFM or NPM.